The interplay between microbial communities and soil properties - Philippot, Laurent; Chenu, Claire; Kappler, Andreas; Rillig, Matthias C; Fierer, Noah (Nature reviews. Microbiology, 2024)
In recent years, there has been considerable progress in determining the soil properties that influence the structure of the soil microbiome. By contrast, the effects of microorganisms on their soil habitat have received less attention with most previous studies focusing on microbial contributions to soil carbon and nitrogen dynamics. However, soil microorganisms are not only involved in nutrient cycling and organic matter transformations but also alter the soil habitat through various biochemical and biophysical mechanisms. Such microbially mediated modifications of soil properties can have local impacts on microbiome assembly with pronounced ecological ramifications. In this Review, we describe the processes by which microorganisms modify the soil environment, considering soil physics, hydrology and chemistry. We explore how microorganism-soil interactions can generate feedback loops and discuss how microbially mediated modifications of soil properties can serve as an alternative avenue for the management and manipulation of microbiomes to combat soil threats and global change.